Pemberdayaan Pasien PPOK melalui Manajemen Diri: Pengembangan dan Uji Coba Buku Panduan Berbasis Written Action Plan - Noviantari, Komang; Isna Amalia Mutiara Dewi; Aat Djanatunisah; Komang Agus Jerry Widyanata (STIKes Hamzar, 2025)
Chronic obstructive pulmonary disease (COPD) remains a significant global health burden. Effective self-management by patients is crucial and involves regular monitoring by healthcare providers, patient education, and a collaboratively agreed-upon written action plan. This study aimed to design and apply a self-management guidebook incorporating a written action plan for individuals with COPD. The study used a pre-experimental design with 9 participants. Data were collected through self-management knowledge questionnaires and evaluations of the guidebook implementation. Results showed a significant increase in self-management knowledge after the intervention (p < 0.05), along with good acceptance from the participants. In conclusion, the written action plan-based guidebook shows promise as a tool to facilitate ongoing care and self-management in COPD patients. Larger-scale studies are recommended to validate these results.